Rencana Pemasaran Jasa Manajemen The Kanjeng Signature Hotels - Victorio, Enrile; Victoria, Gloria Agnes (Journal of Hotel Management, 2024)
The purpose of this research is to create a marketing plan to hotel building and property owners for a brand-new hotel management brand product called “The Kanjeng Signature Hotels”, which is being developed by PT The Kanjeng Indonesia, which headquartered on the island of Bali, Indonesia. The idea of creating this marketing plan is to help the company determine the potential target market, which are the hotel building and property owners, and choose the right marketing strategy to develop the new brand. The theoretical framework is collected by analyzing some of the literature related to tourism and hospitality marketing. From this theory, the right method is selected to implement a marketing plan that will support the company's goals and objectives. The authors decided to use an eight-step process that describes how a marketing plan is implemented. The empirical part includes the author's introduction to the company and its environment by conducting active participatory observations in the company, especially in the business development department, and the company's sales and marketing department. In addition, the quality of the sources from the companies chosen by the author are the founders, shareholders, board of directors and commissioners of the company, who have had qualifications in their respective fields for more than 10 (ten) years, as well as direct discussions with several external parties who related to the company's business. By following the eight-step marketing process guide, the author was able to make the right assumptions for The Kanjeng Signature Hotels marketing plan. The results of the study show that in making a marketing plan for a new brand of hotel management product in a hotel chain requires a lot of research on the company's background, especially the performance of hotels that have already been managed. The research objective in this marketing plan can be concluded that it has been achieved by compiling a marketing plan that provides a reference for the company in its marketing efforts for the new brand to owners of hotel building and property. For further research, companies need to conduct more in-depth studies, especially in the aspects of finance, legality and general administration, product and service standardization, and to always be updated on the latest developments and trends in the tourism and hospitality industry.